2013
DOI: 10.1038/onc.2013.67
|View full text |Cite
|
Sign up to set email alerts
|

Snail depletes the tumorigenic potential of glioblastoma

Abstract: Glioblastoma multiforme (GBM) is an aggressive brain malignancy characterized by high heterogeneity and invasiveness. It is increasingly accepted that the refractory feature of GBM to current therapies stems from the existence of few tumorigenic cells that sustain tumor growth and spreading, the so-called glioma-initiating cells (GICs). Previous studies showed that cytokines of the bone morphogenetic protein (BMP) family induce differentiation of the GICs, and thus act as tumor suppressors. Molecular pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 45 publications
4
57
0
Order By: Relevance
“…The role of EMT factors in glioma pathogenesis is receiving increasing attention. SNAI1 and TWIST1, two main transcriptional activators of the EMT response, have been broadly implicated in glioma progression by a number of groups . We found both to be induced by hypoxia in GBM neurospheres, which is consistent with the reports in other cellular contexts indicating that they can be HIF targets .…”
Section: Discussionsupporting
confidence: 91%
“…The role of EMT factors in glioma pathogenesis is receiving increasing attention. SNAI1 and TWIST1, two main transcriptional activators of the EMT response, have been broadly implicated in glioma progression by a number of groups . We found both to be induced by hypoxia in GBM neurospheres, which is consistent with the reports in other cellular contexts indicating that they can be HIF targets .…”
Section: Discussionsupporting
confidence: 91%
“…ID2 and ID4 have been implicated in this process, as they promote astroglial differentiation in GSCs by downregulating OLIG1/2 (42). The pro-migratory transcription factor Snail is also induced by BMP7 in GSCs, and Snail overexpression decreases GSC tumorigenicity but increases xenograft invasiveness (43), highlighting the complexity of the molecular pathways activated by BMPs. Importantly, OLIG2 is also indispensable for tumor propagation in a PDGF-B-driven mouse model of oligodendroglioma, and the diminished tumorigenic capacity caused by loss of OLIG2 is mimicked by ID4 upregulation (44).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting MT thus can be an efficient way to eradicate CSCs particularly when interfering with ZEB1 signaling as SNAI1 was reported to play divergent roles in stemness and MT. It is reported that SNAI1 in GBM cells promotes invasion but has a negative effect on tumorigenicity, consistent with the ‘go or grow’ hypothesis (Han et al ., ; Savary et al ., ). The fact that EMT‐TFs also regulate various processes in non‐neoplastic CNS stem cells further supports the existence of a stem cell/MT axis during neuro‐oncogenesis.…”
Section: Mt In Tumors Of the Central Nervous Systemmentioning
confidence: 99%